Knowledge and perception of University Of Science Malaysia (USM's) pharmacy students regarding clinical pharmacy specialization / Noor Nadia Ilyana Mohamad Anuar - Mohamad Anuar, Noor Nadia Ilyana (2013)
Principles of clinical pharmacy also involve caring values, knowledge, experience and judgment. Clinical pharmacy also oriented to analysis the population needs related to medicine, ways of administration, and pattern of use and the effect of the drug. Like other outside countries, clinical pharmacy in Malaysia also applying specialization of clinical pharmacy. Objective of this study is to determine the knowledge and perception of University of Science Malaysia's (USM) pharmacy students regarding clinical pharmacy specialization. A survey was conducted using questionnaire instrument design which consists of three sections. The survey was distributed among University of Science Malaysia's (USM) pharmacy students from first year students to final year students in order to measure their knowledge and perception regarding clinical pharmacy specialization. Of 200 distributed surveys, 188 (94%) were returned. From the survey analyzed, the respondents were 52.1 % (n=98) from first year students, 21.8% (n=41) from third year students, and 26.1 % (n=49) from final year students. Overall, 64.4% (n=121) of USM's pharmacy students preferred clinical pharmacy as their division field. USM's pharmacy students' knowledge level was in intermediate zone (neutral) however improvement steps able to overcome this issue. Moreover, the respondents showed positive perception regarding clinical pharmacy specialization as 76.6% (n=144) of them aware that Malaysia is toward clinical pharmacy specialization. As a conclusion, USM's pharmacy students have positive perception towards clinical pharmacy specialization and their level of knowledge can be enriched as these students have high determination for their profession in the future. The positive opinion may be able to change current implementation for development purpose.